The Salish Nephrite/Jade Industry: Ground Stone Celt Production in British Columbia, Canada. (2nd January 2016) - Morin, Jesse
Abstract : The purpose of this paper is to describe the patterns of ground stone celt production in pre-contact southwestern British Columbia (3500 BP–ad 1770) and to offer hypotheses to explain those patterns derived from Coast and Interior Salish ethnographies. The mineralogy of celt production debris and celts was determined using a portable near-infrared spectrometer, and the resulting data mapped using GIS. The spatial distribution of such artifacts clearly indicates that celt production was a highly localized activity in a few centers along the Fraser River, with very little evidence of celt production anywhere else in the Salish British Columbia. Based on this evidence, it is clear that celts were exported in large numbers from very few communities and supplied a market of many hundreds of communities. The patterns evident in such data provide further resolution to the directionality and volume of exchange between celt producing and celt receiving communities. A number of avenues for increasing the volume of production of nephrite celts are explored against the archaeological record. I suggest that elites in nephrite source areas were well-positioned to sponsor or intensify the production of stone celts for export to distant exchange partners.